1999
DOI: 10.1680/gein.6.0140
|View full text |Cite
|
Sign up to set email alerts
|

Bearing Capacity of a Geotextile-Reinforced Unpaved Road as a Function of Deformation: A Model Study

Abstract: An experimental investigation has been carried out to study the bearing capacity of a geotextile-reinforced unpaved road as a function of its deformation. A number of model footing tests were performed on compacted granular fill overlying an artificially sedimented kaolinite layer. The test bed was instrumented to determine the vertical stresses at the fill-subgrade interface. The test results were used to estimate the bearing capacity factors of the foundation as a function of footing deformation. A load tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The empirical approach (1) is valid for Np10000 and a maximum rut depth of 75 mm, or 40 mm with reference to the initial level of the pavement, respectively (Jenner et al, 2002). It is widely applied (Espinoza, 1994;Ingold, 1994;Koerner, 1997) and has proven satisfactory in practice (Jenner et al, 2002;Meyer and Elias, 1999;Som and Sahu, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The empirical approach (1) is valid for Np10000 and a maximum rut depth of 75 mm, or 40 mm with reference to the initial level of the pavement, respectively (Jenner et al, 2002). It is widely applied (Espinoza, 1994;Ingold, 1994;Koerner, 1997) and has proven satisfactory in practice (Jenner et al, 2002;Meyer and Elias, 1999;Som and Sahu, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…3 and 4 show the relationship between the value of LCR and normalized magnitude of two-layer surface displacement calculated on the basis of the experimental results presented by Alenowicz (1989) and Som and Sahu (1999). It is clearly visible that the magnitude of load capacity factors remain practically constant (LCR ¼ 1) for displacements: Up0.1 D/2B (the first case) or Up0.1 D/D (the second case).…”
Section: Article In Pressmentioning
confidence: 79%
“…Results of the research programme performed by Som and Sahu (1999) suggested the significant influence of magnitude of loading on the value of a 0 (Fig. 7).…”
Section: Other Observations-the Load Spread Mechanismmentioning
confidence: 96%
See 1 more Smart Citation
“…One of the most common uses of geosynthetics is in pavement construction, where soft and low-strength soil conditions prevail. In this application, the benefits associated with the use of geosynthetic reinforcement are: (a) to minimize differential and total settlements; (b) to improve the bearing capacity of the soft subsoil; (c) to prevent contamination of the base materials allowing for more open graded, free-draining aggregates; (d) to reduce the pavement thickness; and (e) to extend the service life of the pavement [4,7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Some previous research and experimental studies on sabkha soils have been conducted in the last few decades.…”
Section: Introductionmentioning
confidence: 99%